TRANSFORMASI PEMBELAJARAN: STRATEGI INOVATIF DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Septiana, Dinda; Ali, Muhammad; Jusniati, Andi; Aenil, Nur; Asrisal, Asrisal; Adrian M.R, Muh; Firdaus, Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of innovative learning method interventions on student learning motivation at SMA Negeri 10 Bone. The background of this study is the observed passivity of students during instructional activities, driven by low intrinsic motivation and a monotonous learning climate. This study employed a quantitative approach with a quasi-experimental design involving an experimental class that received innovative learning interventions and a control class that continued with conventional methods. Data were collected through structured observation sheets measuring five indicators of learning motivation across 12 learning sessions. The results indicate that the experimental class showed a significant increase in average motivation from 27.6% to 78%, with an N-Gain of 0.69 in the high category, while the control class only reached 44.2% with an N-Gain of 0.23. Independent sample t-test results showed a significance value (Sig.) < 0.05, confirming that innovative learning method interventions significantly improve student learning motivation. Therefore, the application of varied instructional methods, constructive formative feedback, and a supportive classroom climate is an effective strategy for improving learning motivation in senior high school settings.